2016
DOI: 10.1074/jbc.m116.715359
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcal Nuclease and Tudor Domain Containing 1 (SND1 Protein) Promotes Hepatocarcinogenesis by Inhibiting Monoglyceride Lipase (MGLL)

Abstract: Staphylococcal nuclease and tudor domain containing 1 (SND1) is overexpressed in multiple cancers, including hepatocellular carcinoma (HCC), and functions as an oncogene. This study was carried out to identify novel SND1-interacting proteins to better understand its molecular mechanism of action. SND1-interacting proteins were identified by a modified yeast two-hybrid assay. Protein-protein interaction was confirmed by co-immunoprecipitation analysis. Staphylococcal nuclease and tudor domain containing 1 (SND1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 33 publications
3
37
0
Order By: Relevance
“…Chronic inflammation is a critical event in HCC pathogenesis and induction by inflammatory cytokines might underlie the overexpression of SND1 in human HCC patients. Overexpression and knockdown studies in human HCC cells have demonstrated that SND1 promotes proliferation, migration, invasion and in vivo tumorigenesis [38][39][40][41] . As a component of the RISC in HCC cells, SND1 promotes oncogenic miRNA-mediated degradation of tumor suppressor mRNAs [38] [ Figure 2].…”
Section: Snd1 As An Oncogene For Hccmentioning
confidence: 99%
See 2 more Smart Citations
“…Chronic inflammation is a critical event in HCC pathogenesis and induction by inflammatory cytokines might underlie the overexpression of SND1 in human HCC patients. Overexpression and knockdown studies in human HCC cells have demonstrated that SND1 promotes proliferation, migration, invasion and in vivo tumorigenesis [38][39][40][41] . As a component of the RISC in HCC cells, SND1 promotes oncogenic miRNA-mediated degradation of tumor suppressor mRNAs [38] [ Figure 2].…”
Section: Snd1 As An Oncogene For Hccmentioning
confidence: 99%
“…SND1 induction with TNFα and subsequent profiling of SND1 promoter activity revealed that SND1 regulates a group of glycerolipid metabolic genes including CHPT1, LPGAT1, PTDSS1 and LPIN1 that are involved in biosynthesis of phophatidylcholine, phosphatidylglycerol, phosphatidylserine and triacylglycerol respectively [58] . SND1 interacts with and inhibits monoglycerolipid lipase (MGLL) [41] , a tumor suppressor that converts monoglycerolipids to glycerols and free fatty acids. Thus, SND1 causes an increase in glycerolipid levels in cells by causing an increase in their synthesis or preventing their catabolism in hepatocytes [ Figure 3].…”
Section: Role Of Snd1 In Lipid Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…Nomura et al reported that aggressive cancer lines of various cellular lineages and primary ovarian carcinomas and melanomas may hijack overexpressed MGLL to drive tumorigenesis by remodeling fatty acids to yield a signaling network enriched with pro-oncogenic lipid metabolites such as lipophosphatidic acid and prostaglandins [14]. By contrast, the reduced expression or even absence of MGLL has been reported in various common carcinomas, with MGLL proposed as a potential tumor suppressor [18, 19] because of its growth-suppressive effect on cell colony formation [19]. Notably, contradictory results regarding the oncogenic versus tumor suppressive functions of MGLL have been reported for the same tumor type, such as colorectal cancers [19-21].…”
Section: Discussionmentioning
confidence: 99%
“…However, the regulation of MGLL expression may operate at multiple levels. For instance, MGLL was reported as a potential tumor suppressor in hepatocellular carcinomas, associated with its loss of protein expression, which was posttranslationally dictated by SND1-promoted ubiquitination for proteasome-mediated proteolysis [18]. As revealed in the datasets of cancer genomic projects [22], MGLL amplification is common in various tumor types such as prostatic carcinomas with neuroendocrine phenotypes [23] and pancreatic ductal adenocarcinomas [24].…”
Section: Discussionmentioning
confidence: 99%